Utilizing Intercostal Nerve Autografts for Nipple Neurotization: A Novel Approach to Restore Sensation - Elena Millesi, MD; Christin A. Harless, MD; Vahe Fahradyan, MD; Tina J. Hieken, MD; Mara A. Piltin, DO; Aparna Vijayasekaran, MBBS (Plastic and Reconstructive Surgery, Global Open)
Summary:. Breast cancer is a common malignancy, and treatment often involves mastectomy. For oncological safety, the anterior and lateral cutaneous branches of the third through fifth intercostal nerves are routinely resected during nipple-sparing mastectomies, leading to loss of nipple sensation. The current gold standard for nipple neurotization uses nerve allografts to connect the nipple with a remaining stump of an intercostal nerve. Despite the convenience of off-the-shelf solutions, this study explored a novel approach using intercostal nerves as autografts or for direct repair to restore nipple sensation. Six patients underwent nipple-sparing mastectomy and opted for nipple neurotization. Three patients underwent neurotization with an intercostal nerve autograft, whereas in 3 patients, long intercostal nerves allowed nipple neurotization directly without the need for an autograft. Meticulous dissection of the intercostal nerves enabled a length of approximately 9 cm (±1.5) per nerve. The acquired nerve length allowed tension-free coaptation of direct nipple neurotization in 3 patients and utilization as an autograft in the other 3 patients. No postoperative complications were observed, whereas sensory outcomes are yet to be evaluated. The study highlighted the feasibility of using intercostal nerves either as autologous intercostal nerve grafts or for direct neurotization. Using an intercostal nerve as an autograft is a cost-effective and time-efficient strategy to avoid the need for an allograft without additional donor-site morbidity. This technique offers a practical and globally accessible solution for improving patient access to state-of-the-art postmastectomy breast reconstruction.